Myelin basic protein and its diagnostic value in HIV-infected individuals with 4th clinical stage and neuroinfections - Kozko, Volodymyr; Hvozdetska-Shaar , Maryna; Sokhan, Anton; Yurko, Kateryna; Solomennyk, Ganna (ScienceRise: Medical Science, 2021)
It was shown that in HIV-infected patients, pathomorphological changes in the white matter in the form of demyelinization are already observed in the early stages of the disease. The most studied marker of this process is myelin basic protein that can be detected in cerebrospinal fluid or serum immediately after acute myelin breakdown. The aim. To assess the diagnostic value of myelin basic protein content in serum and cerebrospinal fluid of HIV-infected individuals with 4th clinical stage and central nervous system opportunistic infections. Materials and methods. Using ELISA with diagnostic kit “MBP ELISA” (Ansh Labs, USA), we studied the myelin basic protein content in serum and cerebrospinal fluid of 53 HIV-infected patients with 4th clinical stage and central nervous system opportunistic infections depending on its etiology, the outcome of the diseases and according to Glasgow coma scale score. As well correlation analysis with some laboratory and clinical indicators was performed. Results. We found significantly increased myelin basic protein content in both cerebrospinal fluid and serum of HIV-infected patients 4th clinical stage with central nervous system opportunistic infections compared to control (p˂0.01), which indicate the presence of active demyelinization in central nervous system. The highest cerebrospinal fluid myelin basic protein was registered in patients with an unfavourable outcome of the disease, as death or residual neurologic deficit, and patients with cerebral toxoplasmosis. The cerebrospinal fluid myelin basic protein had an association with the size of white matter lesions on magnetic resonance imaging and serum myelin basic protein content. Conclusions. Myelin basic protein detection in cerebrospinal fluid as well as in serum can serve as an additional quantitative marker of myelin disruption, which can be used along with magnetic resonance imaging for the diagnosis improvement and prognosis of central nervous system opportunistic infections in HIV-infected individuals with 4th clinical stage